Analiza niezawodności wybranych konstrukcji oporowych - Rybak, Jarosław (Reliability analysis of selected retaining structures, 2002)
The work is divided into three parts: chapters 1, 2 and 3 contain motivation, presentation of the problem and definition of the aim of the work as well as literature studies describing the current state of knowledge along with the author’s comments, chapters 4 and 5 present the assumptions and results of the numerical calculations, chapter 6 contains conclusions from the calculations along with a comparison and discussion of the results cited and constituting the author’s original work.
Keywords: konstrukcja oporowa; niezawodność; normalizacja; ścianka szczelna; ściana szczelinowa; retaining structure; reliability; standardization; sheet pile wall; diaphragm wall